1993
DOI: 10.1126/science.260.5105.204
|View full text |Cite
|
Sign up to set email alerts
|

Velocity Structure of a Gas Hydrate Reflector

Abstract: Seismic reflection profiles across many continental margins have imaged bottom-simulating reflectors (BSRs) parallel to the seabed; these are often interpreted as the base of a zone in which methane hydrate "ice" is stable. Waveform inversion of seismic reflection data can be used to estimate from seismic data worldwide the velocity structure of a BSR and its thickness. A test of this method at a drill site of the Ocean Drilling Program predicts that sediment pores beneath the BSR contain free methane for appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
167
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 250 publications
(170 citation statements)
references
References 16 publications
2
167
0
1
Order By: Relevance
“…Previous studies suggest that most of the BSR amplitude is due to the velocity reduction of the underlying free gas (Singh et al, 1993;MacKay et al, 1994;Hyndman et al, 2001;Pecher et al, 2001). The presence of a free-gas zone (FGZ) is an important part of the gas hydrate system, and is particularly important if the presence of gas hydrate is to be…”
Section: Geophysical Explorationmentioning
confidence: 99%
“…Previous studies suggest that most of the BSR amplitude is due to the velocity reduction of the underlying free gas (Singh et al, 1993;MacKay et al, 1994;Hyndman et al, 2001;Pecher et al, 2001). The presence of a free-gas zone (FGZ) is an important part of the gas hydrate system, and is particularly important if the presence of gas hydrate is to be…”
Section: Geophysical Explorationmentioning
confidence: 99%
“…BSRs are generally caused by gas at the base of the gas hydrate stability zone (Singh et al 1993), a phase boundary determined by pressure and temperature conditions. BSRs in seismic data are therefore subparallel to the seafloor, often crosscutting the stratigraphic structure.…”
Section: Introductionmentioning
confidence: 99%
“…The seismic reflection data off K-G basin (Collett et al, 2008;Dewangan et al, 2010;Shankar and Riedel, 2010) show regional presence of gas hydrates manifested in the form of bottom simulating reflectors (BSR) observed at depth of 125 mbsf (water depth: 945m) to 220 mbsf (water depth 1146 m). BSRs represent a phase boundary, where the low-velocity, gas-charged sediments occur below the high-velocity gas hydrate bearing sediments (Singh and Minshull, 1993). Ramana et al (2007) and Dewangan et al (2010) have reported various shale tectonics induced structures like bathymetric mounds, deep seated shale diapirs and toe thrust faults from the K-G basin.…”
Section: Geological Settingmentioning
confidence: 99%